The Effect of International Financial Reporting Standards (IFRS) Adoption on Conditional Conservatism: A Study on BİST 100 - Azarifar, Darioush (Business, Marketing, and Finance Open, 2024)
International Financial Reporting Standards (IFRS) have been prepared in order to prepare the financial statements of transactions operating in different countries using a common financial language, and also to enable investors from all over the world to evaluate the financial statements in question with a standard perspective. In Türkiye, Turkish Accounting-Financial Reporting Standards (TMS-TFRS) have been published in line with the International Financial Reporting Standards, which aim to present current values instead of the historical cost approach and are based on fair value. After this change, the differences in the accounting practices, presented financial information and presentation styles of the enterprises have been a natural result of this process. As a result of the change that comes with TFRS, it is known that there is a change in the degree of conservatism of enterprises, especially in the degree of conditional conservatism. In this study, the effects of the adoption to TFRS on the financial reporting system of enterprises in Türkiye were evaluated in terms of the degree of conditional conservatism. The data of a total of 41 enterprises, 34 of which belong to the Manufacturing Sector and 7 of which belong to the Service Sector, were selected as a sample between the years 2000-2018. The period between 2000-2004, the financial reporting system based on historical costs; the period between 2005-2018 represents the financial reporting system in line with TFRS. The method applied in the study to determine the effect statistically is the method of Panel Data Analysis. According to the extended Basu (1997) model used to determine the degree of conditional conservatism, after the adoption of TFRS, it is seen that there is a decrease in the degree of conditional conservatism of the enterprises in each of the Manufacturing Sector, Service Sector and All Businesses. In other words, as a result of the study, it has been determined that the transition to TFRS has a negative effect on the level of conservatism.